The Effect Of Traditional Engklek Game Based On Problem Based Learning Model On Improving Crithical Thinking Ability Of Elementary School Students In Science Subjects - Nisfah Lailla Handarizki; Angga Setiawan; Indah Yunitasari (JOSAR (Journal of Students Academic Research), 2025)
Twenty-first-century education demands a transformation in teaching strategies, with a focus on cultivating higher-order thinking skills, especially critical thinking. Observations and interviews at SD Negeri 2 Bendoagung, SD Negeri 3 Bendoagung, and SD Negeri 2 Karangrejo revealed that students' critical thinking skills are still relatively low. One of the underlying causes is the application of instructional methods that fail to sufficiently stimulate critical thinking. This study seeks to investigate the effect of incorporating traditional engklek games into a Problem-Based Learning (PBL) model on students’ critical thinking abilities in science education. The research employed a quantitative method with a quasi-experimental approach, specifically using a nonequivalent control group design. The sample was selected purposively, involving fourth-grade students from SD Negeri 2 and 3 Bendoagung as the experimental group, while students from SD Negeri 2 Karangrejo acted as the control group. Data were gathered using a critical thinking test, and analyzed using normality and homogeneity tests, followed by an independent sample t-test. Results showed a significant improvement in the experimental group, with a 46.55% increase in critical thinking performance, compared to only 11.11% in the control group. The hypothesis test produced a significance (2-tailed) value of 0.000, which is below the 0.05 threshold indicating that the integration of traditional engklek games within a PBL framework has a positive impact on students’ critical thinking skills.